Optimal environmental policy, public goods and labor markets over the business cycle - Grodecka, Anna; Kuralbayeva, Karlygash (Oxford, 2014)
"This paper studies the design of optimal fiscal policy in a real business cycle model with distortionary taxes and a climate change externality. Governments face the dual task of internalizing environmental externalities and raising revenues to finance the provision of public goods, including public capital. At their disposal governments have access to two tax instruments: tax on emissions and labor tax. We find that a tax on labor is an efficient instrument to finance public spending and facilitate the adjustment of the economy to the temporary improvement in productivity. Therefore, labor tax is cut in the model. Tax on emissions follows a distinct pattern depending on whether the potential economic expansion in response to a positive productivity shock is strong or weak: it is procyclical in the model that features public capital and is countercyclical in the models with public consumption only. The model implies that by restraining or boosting expansion in the short-run, the optimal carbon tax policy can help policy makers reconcile short-term concerns over economic growth with longer-term risks from climate change. The welfare gains from such short-run policies are non-negligible and can amount to USD 121.9bn or 0.7% of the US GDB."